2019
DOI: 10.1007/978-3-030-14409-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Rural Livelihood Challenges: Moving out of Agriculture

Abstract: In this chapter, we deliberate upon the role of the non-farm sector in the food systems. We argue that livelihood diversification in rural India would lead to an overall economy-wide increase in productivity, and facilitate swifter structural transformation and poverty reduction. We highlight the role of the non-farm sector for job creation in rural areas, especially along the rural-urban continuum for structural transformation to take place. Policy has not yet leveraged the potential of small towns and the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The government should give technical products and ample extension services, and offer subsidies to achieve a considerable breakthrough in the agricultural sector. Pingali, Aiyar, Abraham and Rahman (2019) reported that the rural-urban movement with the growing urbanization has led farmers to slowly desert farming, particularly among the young rural workers. In many nations, the main laborers engaging in agriculture have progressively altered from the young to the old.…”
Section: Stratford Peer Reviewed Journals and Book Publishing Journal...mentioning
confidence: 99%
“…The government should give technical products and ample extension services, and offer subsidies to achieve a considerable breakthrough in the agricultural sector. Pingali, Aiyar, Abraham and Rahman (2019) reported that the rural-urban movement with the growing urbanization has led farmers to slowly desert farming, particularly among the young rural workers. In many nations, the main laborers engaging in agriculture have progressively altered from the young to the old.…”
Section: Stratford Peer Reviewed Journals and Book Publishing Journal...mentioning
confidence: 99%
“…For example, ILO (2019) argues that diversification of rural economy in agricultural activities and non-agricultural activities has significant potential to reduce poverty, increase the ability of rural people to cope with the volatility of agricultural commodity prices, strengthen food security and improve the quality of life in rural areas. Pingali et al, (2019) also stressed the importance of the role of economic diversification in bringing positive change to rural areas. In this context, he argues that economic diversification in rural areas can lead to overall productivity increase, drive Community: volume 6, nomor 2, Oktober, 2020 p-ISSN: 2477-5746 e-ISSN: 2502-0544 structural transformation and eradicate poverty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the years, people living in the forest and savannah communities across Africa rely on the natural environment for their livelihoods: with food crop production, livestock and agro-processing being dominant sources. Beyond the rural areas, traditional livelihoods are more diversi ed, extending from non-farm activities to a wide range of services (Pingali et. Al, 2019).…”
Section: Introductionmentioning
confidence: 99%